UMP to drive forward with Social Enterprise Technological University concept VC - UMP, PNC (2019)
Universiti Malaysia Pahang (UMP) looks forward to move ahead with its ‘Social Enterprise Technological University’ concept to ensure long-term self-sustainability, and reduce its